Функции этнической культуры в эпоху «нового регионализма» (социально-философский анализ) - Емельянова, Юлия Павловна; Ємельянова, Юлія Павлівна; Yemelianova, Yuliia (Східноєвропейський національний університет імені Лесі Українки, 2019)
Анализируются функции этнической культуры в эпоху завершения очередной волны глобализации и начала эпохи мультирегионализма или «нового регионализма». Национальные государства утрачивают ряд своих важных функций, в том числе социального гаранта и носителя общенациональной социальной перспективы. Обесценивание концепта нации приводит индивидов к актуализации фундаментальной формы солидарности – этнической. Генерализация концепта культуры в постнеклассической эпистемологии позволяет предложить авторское объяснение механизмов этнокультурной конвергенции и регионализации как глубинный этносоциокультурный процесс. Этническая культура показана генератором ритмов социальной динамики этносов, которые поддерживают ее главную функцию – формирование и сохранение индивидуально-личностной субъектности индивида-этнофора. The article considers and analyzes the phenomenon of ethnic culture in the modern social process. Sociology marks the end of another wave of globalization and the beginning of the formation of local resources, which are accompanied by significant social functions of modern states. The main social institutions are publicly accessible social prospects, etc. Inflation of system-forming functions leads to the fact that individuals actualize the fundamental form of solidarity – the ethnic solidarity. Two contradictory processes – the disintegration of nations as the leading social communities of the 20th century, and the activation of ethnic group consciousness – form new sociocultural constructs, analyzing which sociology announces the beginning of an era of multiregionalism or «new regionalism». In search of a theoretical explanation of the mechanisms of this process, the author refers to the concept of culture and related concepts such as «ethnic culture», «core culture», «ethno-sociocultural system», etc. The generalization of the concept of culture and post-non-classical epistemology allows us to explain the mechanisms of ethnocultural convergence and regionalization as a deep ethno-sociocultural process. This process presupposes the existence of a multitude of local ethno-cultural subjects, deprived of objectivity and legitimizing acts, but capable of narrowing or increasing their social influence. The generator of the rhythms of the social dynamics of ethnic groups is the ethnic culture, which has among its functions the main one – the function of forming the individual personality subjectivity of a person.
The Functions of Ethnic Culture in the Era of the «New Regionalism» (Socio-Philosophical Analysis)
Функції етнічної культури в епоху «нового регіоналізму (соціально-філософський аналіз)
Keywords: глобализация; регион; локализация; культура; этносоциокультурная система; globalization; region; glocalization; culture; ethno-socio-cultural system